2008
DOI: 10.1590/s0102-09352008000600024
|View full text |Cite
|
Sign up to set email alerts
|

Controle autonômico da freqüência cardíaca em Spilotes pullatus (Colubridae) como determinante das respostas de medo

Abstract: RESUMONeste estudo, investigaram-se as modificações fisiológicas em Spilotes pullatus, como determinantes das respostas ao medo, obtidas pela exposição ao eletrocardiograma. Foram utilizadas quatro serpentes com média de peso de 0,5±0,06kg. Dois minutos após a fixação dos eletrodos, as serpentes apresentavam-se imóveis, com redução significativa na freqüência cardíaca e aumento nos intervalos PQ, QRS, RR e RT (P<0,05). Os resultados sugerem que a presença de sintomas de medo pode gerar riscos à saúde desses an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 11 publications
(8 reference statements)
1
4
0
Order By: Relevance
“…Valentinuzzi et al, (1970) observed considerable variation in the T wave amplitude and duration over several days in snakes, although no immediate apparent cause of such variations was identified. The values for the ECG parameters in P. guttatus were lower than those for other species such as Boa constrictor (Conceição et al, 2014;Armelin et al 2019), Lampropeltis getuhts (Valentinuzzi et al, 1970) and Eunectes murinus (Strussmann, and Sazima,1991), but similar to those reported for Spilotes pullatus (Cruz and Junkes, 2008) and Crotalus durissus (Stuginski et al, 2011).…”
supporting
confidence: 70%
See 4 more Smart Citations
“…Valentinuzzi et al, (1970) observed considerable variation in the T wave amplitude and duration over several days in snakes, although no immediate apparent cause of such variations was identified. The values for the ECG parameters in P. guttatus were lower than those for other species such as Boa constrictor (Conceição et al, 2014;Armelin et al 2019), Lampropeltis getuhts (Valentinuzzi et al, 1970) and Eunectes murinus (Strussmann, and Sazima,1991), but similar to those reported for Spilotes pullatus (Cruz and Junkes, 2008) and Crotalus durissus (Stuginski et al, 2011).…”
supporting
confidence: 70%
“…Clinically, HRV analysis can be used to detect changes in cardiac function and neuronal activity that may be indicative of the animal´s general health, with a high HRV indicating a well-regulated system and a low or reduced HRV indicating potential health problems; such analyses can improve the interpretation and management of heart disease in reptiles (Veras and González, 1999;Veras et al, 2000;Wang et al 2003;Cruz and Junkes, 2008;La Rovere et al, 2012;Gemer, 2016;Shaffer and Ginsberg, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations